Pengaruh Leverage, Profitability, Sales Growth, dan Firm Size Terhadap Tax Avoidance - Setiawan, Adi Tri; Putranto, Panji (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 2 (2025): Jurnal Online Insan Akuntan (Desember 2025)DO - 10.51211/joia.v10i2.3563, 2025)
The objective of this research is to test and analyze the effect of leverage, profitability, sales growth, and firm size on tax avoidance. The research method employed a quantitative approach. The present study utilizes secondary data, specifically financial statements of manufacturing companies in the consumer non-cyclical sector that are listed on the Indonesia Stock Exchange. The research population comprised 97 manufacturing companies in the Consumer Non-Cyclicals Sector that were listed on the Indonesia Stock Exchange during the period 2020-2023 with a purposive sampling technique was employed to obtain a sample of 47 companies. In this study, the object of analysis consists of the observed variables, namely leverage, profitability, sales growth, and firm size, which function as independent variables, and tax avoidance, which functions as the dependent variable. The data was analyzed using panel data regression with the aid of EViews 10 software. The results showed that profitability and sales growth have a significant positive effect on tax avoidance. While leverage and firm size don’t have a significant influence on tax avoidance. These results contribute to regulators, especially the Direktorat Jenderal Pajak, to review the level of company profitability in the audit process for corporate tax avoidance.